Prescribing Trends of Antidiabetic Drugs in Type 2 Diabetes Mellitus Patients With Chronic Kidney Disease (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Patients suffering from Type 2 Diabetes Mellitus with chronic kidney disease is increasing in recent years. There is lack of studies on the prescribing trends of antidiabetic drugs in our country regarding Type 2 Diabetes Mellitus with chronic kidney disease patients. The aim of this study was to assess the prescribing trends of antidiabetic drugs in Type 2 Diabetes Mellitus with chronic kidney disease patients.Materials and methods: A cross sectional study was performed from July 2022 to June 2023, by analyzing patients attending OPD of Endocrinology and Nephrology Department of SSMCMH and BIRDEM. Total 344 participants were enrolled after meeting the selection criteria.Results: Mean age of the participants was 65.6 years with a male gender predominance (55.2%). Mean HbA1c was 7.40. Majority of the participants (39.5%) were in stage 3b. DPP-4 inhibitors were frequently prescribed as single drug (23.5%) and also SGLT2 inhibitors (16.0%). Among the combination therapy, insulin + DPP-4 inhibitor (28.8%) was used mostly prescribed followed by metformin + SGLT2 inhibitor (12.5%).  Conclusion: In our study the combination of metformin and SGLT 2 inhibitor were found to be used less frequently. Nonetheless, it is evident that its utilization was lesser in the previous year than it is currently. Thus, we can conclude that this medications have been used more frequently in recent years.JCMCTA 2024 ; 35 (2) : 100-104